Sauer's manual of skin diseases - Hall, Brian J. (Brian John) 1981- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
This book provides step-by-step instructions and algorithms for diagnosis and treatment of all common skin conditions. Unique features include more than 700 full-color photographs; diagnostic algorithms based on site and type of lesion and age of patient; and a comprehensive dictionary-index of skin diseases. This thoroughly revised, updated Tenth Edition includes new chapters on sexually transmitted infections, non-melanoma skin cancer, vascular tumors, cutaneous T-cell lymphoma, skin diseases in ethnic skin, obesity and dermatology, skin diseases in transplant patients, and nutritional and metabolic diseases and the skin.